Efektifitas Terapi Rendam Kaki Dengan Air Hangat Terhadap Penurunan Tekanan Darah Pada Ibu Hamil - Yulianti, Silvia; Handayani, Lisda; Noval, Noval (USADA NUSANTARA : Jurnal Kesehatan Tradisional, 2024)
High blood pressure in pregnancy is a high blood pressure disease that occurs during pregnancy and usually in the last month of pregnancy or more after 20 weeks of gestation in women who were previously normotensive. Warm water soak therapy is conductive where heat transfer from warm water into the body will cause dilation of blood vessels and decreased muscle tension, so as to improve blood circulation. The purpose of the study was to determine the effectiveness of foot soak therapy with warm water on reducing blood pressure in pregnant women in the Murung Pudak Health Center Work Area. The research method uses pre-experimental experiments, with a research design in the form of one group pretest-posttest without control. The results of the study that giving warm water foot soak reduced systolic blood pressure in pregnant women in the work area of the Murung Health Center and diastolic blood pressure before and after warm water foot soak therapy on reducing blood pressure there was a significant difference (p = 0.014, ≤ 0.05), so it can be concluded that giving warm water foot soak can reduce diastolic blood pressure in pregnant women.